Neuromodulatory effects of Calyptranthes grandifolia extracts against 6-hydroxydopamine-induced neurotoxicity in SH-SY5Y cells - Kich, Débora Mara (2021)
Alzheimer’s and Parkinson's diseases are neurodegenerative disorders characterized by progressive neuronal dysfunction. Previous studies revealed that some natural products have neuroprotective properties, including species of the Myrtaceae family. However, the neuromodulatory potential of Calyptranthes grandifolia is not clear. In the present study, we examined the ability of the ethanol and hexane leaf extracts of C. grandifolia to prevent 6-hydroxydopamine (6-OHDA)-induced neurotoxicity in vitro. Initially, we investigated the potential of the extracts to inhibit the neurodegenerative-related enzymes c-Jun N-terminal kinase 3 (JNK3) and acetylcholinesterase (AChE). In addition, SH-SY5Y cell viability was assessed by MTT assay after 100 mM 6-OHDA-induced cell damage. In order to verify the possible effects of both extracts on 6-OHDA-induced cell death, hydrogen peroxide generation, mitochondrial potential and caspases-3 activity were assessed. Our findings revealed that ethanol extract exhibited inhibitory activity against JNK3 and AChE. In addition, when co-treating SH-SY5Y cells with 6-OHDA and the extracts, oxidative stress was inhibited by both extracts through a decrease of mitochondrial depolarization and caspases-3 activity. In summary, ethanol and hexane extracts of C. grandifolia have some suppressive property against neurotoxicity induced by 6-OHDA.